Business plan: Eco-Auto Spa / Nur Liyana Kamaruddin ... [et al.] - Kamaruddin, Nur Liyana; Abdul Rahim, Rosilah; Kamaruddin, Irrawanita; Akram Sidek, Muhammad Amir; Raja Azrav, Raja Syazreen Elyda (2018)
1.1 Name of Company : Eco-Auto Spa Services 1.2 Nature of Business : We provides vehicle cleaning services for people around the premises at an economical price. The services we offer are affordable where customers can choose the special packages available and become our club members to get cheaper prices. 1.3 Location of Business : No. 37, Ground Floor, Jalan Kristal L7/L, Seksyen 7, 40000 Shah Alam, Selangor. 1.4 Date of Business Commencement: August 2018 1.5 Future prospect of the Business : 1) To widen the target market. We want to open a new branch in another state location. 2) To introduce our vehicle cleaning services as well-known services in Malaysia. With the professional services that we provide, customers can enjoy clean and shine vehicles at reasonable prices. A great place to wash your vehicle! 3) To have a highly demand in the market and be able to compete with others competitor that existed in the market nowadays